2015
DOI: 10.14257/ijunesst.2015.8.11.21
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Confidence in Newborn Care and Postpartum Fatigue of Puerperal Mothers in Rooming-in vs. Non-rooming-in Groups

Abstract: Scale, comfort & safety (t=2.876, p=.005), feeding (t=2.281, p=.024), infant's behavior (t=2.395, p=.018), hygiene control (t=2.978, p=.003), p<.001) and confidence in newborn care showed significant total scores (t=2.997, p=.003). Based on the Fatigue Continuum Form, the physical, psychological, and neurosensory fatigue scores and the total fatigue score did not show any statistical significance in each area (t=1.169, p=..244)(t=1.941, p=.054)(t=1.863, p=.064)(t=1.897, p=.060). The present findings can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Additionally, the results showed that postpartum women who gave birth at rooming-in facilities experienced a higher level of fatigue than postpartum women who gave birth at nonrooming-in facilities. These results are in line with study results conducted in Korea, which found that women in rooming-in settings had a significantly higher level of fatigue than women who partially apply roomingin (14) .On the other hand, other studies demonstrated no significant differences between groups in term of postpartum fatigue [9,10] .The inconsistent results about postpartum fatigue might be related to the different times of data collection, and the varying fatigue scales that were used in measuring it among postpartum women. The consensus regarding a unifying and universal fatigue scale is warranted to enable the researchers to assess fatigue level among postpartum women.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Additionally, the results showed that postpartum women who gave birth at rooming-in facilities experienced a higher level of fatigue than postpartum women who gave birth at nonrooming-in facilities. These results are in line with study results conducted in Korea, which found that women in rooming-in settings had a significantly higher level of fatigue than women who partially apply roomingin (14) .On the other hand, other studies demonstrated no significant differences between groups in term of postpartum fatigue [9,10] .The inconsistent results about postpartum fatigue might be related to the different times of data collection, and the varying fatigue scales that were used in measuring it among postpartum women. The consensus regarding a unifying and universal fatigue scale is warranted to enable the researchers to assess fatigue level among postpartum women.…”
Section: Discussionsupporting
confidence: 89%
“…As they can observe nurses while providing care for the baby beside mothers, and asking for help and advice on issues related to baby care. Women in the rooming-in settings experience a higher level of confidence while providing care for their newborns [10] .The study results demonstrated no significant differences between the women in the rooming-in group and the women in the non-rooming-in group in the difficulty in doing the baby care activities. Both groups demonstrated a low level of difficulty.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations